(untitled) (New York, 2002)
This book is mainly directed towards postgraduate students and professionals in the field of research and implementation of integrated pest and disease management programmes in greenhouse crops. After presenting the major pests and diseases that affect greenhouse vegetable and ornamental crops, several chapters deal with the tools for designing and implementing IP&DM in protected cultivation with particular emphasis on biological control. Current implementation and the future of IP&DM in the most important protected crops world-wide are presented in the concluding chapters
Keywords: Greenhouse plants,Nhà kính; Diseases and pests,Integrated control,Bệnh và sâu